PIPE-PERITONEAL FORM OF INFERTILITY: ETIOLOGY, RISK FACTORS, MODERN METHODS OF TREATMENT - Гребенникова, Эльвира Константиновна; Григорян, Эвелина Саркисовна; Цхай, Виталий Борисович; Брехова, Ирина Сергеевна; Костарева, Ольга Васильевна; Домрачева, Марина Яковлевна (Mother and Baby in Kuzbass, 2019)
To date, there are many studies on the treatment of tubal-peritoneal infertility. Analysis of the literature suggests that currently in the treatment of women suffering from tubal infertility, two options are available: surgical treatment and assisted reproductive technologies. Numerous studies of domestic and foreign literature indicate that, to date, the problem of effective treatment of tubal-peritoneal infertility remains unresolved until the end. Also for family planning, the problem of assessing the ovarian reserve and reducing the follicular pool after surgery on the fallopian tubes remains unmet and unstudied.
Keywords: infertility; surgery; postoperative adhesions